The Effect of Foam Rolling Duration on Hamstring Range of Motion - Couture, Grace (Open Orthop J, 2015)
Musculoskeletal health benefits from flexibility training and maintaining a functional, or sport specific, range of motion is important to one’s overall fitness. Commercial foam rollers are commonly used in gyms, therapy clinics and homes, yet data are lacking on the optimal rolling duration and effect on range of motion. PURPOSE : The purpose of this study was to examine the effect of varied durations of a commercial foam roller treatment on hamstring range of motion. METHODS : The knee extension range of motion of 33 college aged men and women (age= 20±1.5y, mass= 72.2±10.8 kg) was assessed after a short (2 sets of 10s) and long (4 sets of 30s) duration of hamstring self-administered myofascial release using a commercial foam roller. A one way ANOVA was performed to compare the mean knee extension angle for each condition to baseline measures. RESULTS : Results indicated that neither the short duration (67.30 ± 10.60 deg) nor long duration (67.41 ± 10.81 deg) rolling condition produced significant increases in knee extension compared to baseline (67.70 ± 9.90 deg). CONCLUSION : Self-administered foam rolling for a total duration of up to 2 minutes is not adequate to induce improvements in knee joint flexibility. Contributing factors may include the amount of pressure imparted by the commercial roller as well as duration of treatment.